2017
DOI: 10.1038/pr.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

NOX-mediated impairment of PDGF-induced DNA synthesis in peripheral blood lymphocytes of children with idiopathic nephrotic syndrome

Abstract: BackgroundCellular oxidative stress, inflammatory responses, and immunogenic events are involved in pathogenesis of idiopathic nephrotic syndrome (INS); however, the exact mechanism remains unknown. We examined NADPH oxidase (NOX) activity and platelet-derived growth factor (PDGF)-induced DNA synthesis in peripheral blood lymphocytes (PBL) of patients with INS.MethodsPBL from 15 patients with INS and 15 age- and gender-matched controls were isolated, and enzyme activities of NOX, catalase, and superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Among them, NOX are known to regulate the differentiation and self-renewal of stem cells and potentiate the self-renewal, metastasis, and drug resistance of CSCs through, for example, Notch, mitogen-activated protein kinases (MAPKs, including Erk1/2, Jun N-terminal kinase (JNK), and p38 kinase), and phosphatidyl-inositol-3-kinase- (PI3K-) AKT signaling ( Skonieczna et al, 2017 ). Crosstalk between NOX and the signaling of TGFβ1 ( Ning et al, 2002 ), BMP ( Sanchez-De-Diego et al, 2019 ), Ang II ( Nguyen Dinh Cat et al, 2013 ), PDGF ( Al-Eisa and Dhaunsi, 2017 ), EGF ( Weng et al, 2018 ), and IGF-1 ( Xi et al, 2013 ; Kang et al, 2016 ) has also been reported and/or reviewed. Moreover, NOX potentiate the interaction between ECM and cell surface receptors such as integrin β1 ( Heo and Lee, 2011 ), thereby facilitating cell adhesion and migration, particularly in the presence of niche cytokine factors such as IGF-1 ( Chiarugi et al, 2003 ; Meng et al, 2008 ; Heo and Lee, 2011 ; Xi et al, 2013 ).…”
Section: Main Textmentioning
confidence: 99%
“…Among them, NOX are known to regulate the differentiation and self-renewal of stem cells and potentiate the self-renewal, metastasis, and drug resistance of CSCs through, for example, Notch, mitogen-activated protein kinases (MAPKs, including Erk1/2, Jun N-terminal kinase (JNK), and p38 kinase), and phosphatidyl-inositol-3-kinase- (PI3K-) AKT signaling ( Skonieczna et al, 2017 ). Crosstalk between NOX and the signaling of TGFβ1 ( Ning et al, 2002 ), BMP ( Sanchez-De-Diego et al, 2019 ), Ang II ( Nguyen Dinh Cat et al, 2013 ), PDGF ( Al-Eisa and Dhaunsi, 2017 ), EGF ( Weng et al, 2018 ), and IGF-1 ( Xi et al, 2013 ; Kang et al, 2016 ) has also been reported and/or reviewed. Moreover, NOX potentiate the interaction between ECM and cell surface receptors such as integrin β1 ( Heo and Lee, 2011 ), thereby facilitating cell adhesion and migration, particularly in the presence of niche cytokine factors such as IGF-1 ( Chiarugi et al, 2003 ; Meng et al, 2008 ; Heo and Lee, 2011 ; Xi et al, 2013 ).…”
Section: Main Textmentioning
confidence: 99%
“…In addition to ROS, biomarkers of antioxidants, including SOD, 9,[11][12][13]21,22 catalase, 21,22 glutathione peroxidase, 13,21,23 vitamin A, 23 vitamin C, 9,23 vitamin E, 9,23 carotene, 10 and riboflavin, 10 have been extensively studied in pediatric INS patients to clarify the involvement of decreased antioxidant potential in pathogenesis of the disease. In almost all studies, compared with healthy controls, antioxidant biomarkers were lower in INS patients when they had advanced proteinuria.…”
Section: The Association Between Oxidative Stress and Insmentioning
confidence: 99%
“…It has been reported that NADPH-oxidase family members, in particular NOX1 and NOX4, are expressed by cancer cells and promote tumor growth and metastasis in several cancers (i.e., melanoma, gastric, pancreatic, and colorectal cancers) [20]. They are also expressed by the cellular components of blood vessels (e.g., endothelial cells, pericytes, and vascular smooth muscle cells) and promote tumor angiogenesis [21][22][23][24]. Interestingly, the pharmacologic inhibition of NOX1, using a selective NOX1 inhibitor (GKT771) and NOX1 genetic ablation in mice, demonstrated potent anti-tumor and anti-angiogenic activities [25].…”
Section: Introductionmentioning
confidence: 99%